Attributes of credit cards that lead - Johnson, Karen (My University, 2011)
Purpose of the study - The purpose of the study was to identify what the attributes of a credit card were that consumers found desirable and that led to acquisition of a particular credit card. Further analysis was conducted to identify whether there were any differences or preferences for these attributes according to certain demographics of the consumer. Design / Methodology – Conjoint Analysis was used to allow members to identify what product bundle they preferred. This was done using hypothetical credit cards that consumers were asked to rate on a scale of 0 – 10. This rating was done during 150 face to face interviews. The data from these interviews was then analysed using Sawtooth market simulator which makes it possible to identify which attributes and utilities were the most attractive to the consumer. Further studies using One way ANOVA and a Two sample T –test was used to identify demographics differences. Findings – On average, consumers found the source of the card to be the most important factor when choosing a credit card, and the financial components of a credit card were more important on average than the value added benefits. Preference for these attributes and utilities was significantly influenced by household income with marital status and age showing less influence in the preference of certain attributes and utilities. Interestingly, the way people pay their cards, whether they were revolvers or convenience users, has shown to have very little impact on the attributes that they prefer in a credit card. Value – Despite the growth of credit cards in the South African market in recent years, there seems to be little research in South Africa about why consumers would choose a particular credit card. Introduction of the National Credit Act (no 34 of 2005) has also caused people to become more discerning about the credit that they choose to carry, meaning that the credit card issuer needs to ensure that their cards are appealing and attractive to the market that they are trying at reach. This study intends to close that gap
MBA - WBS
Keywords: Credit cards